Review Article: Presepsin: New Biomaker to Evaluate Empirical Antibiotic Therapy Outcome in Septic Condition - Puspitasari, Aldita Cahyani; Mawari, Ayu (Folia Medica Indonesiana, 2020)
This review presents key publications from the research field of new biomarker of sepsis and other relevant journals during 2009-2015. The results of these experimental studies and clinical trials are discussed in the context of biomarker for sepsis and the accuracy of presepsin for optimising antibiotic therapy. The discussion highlights and summarises articles on three main topics: diagnostic and prognostic biomarkers, presepsin as new biomarkers, and outcome studies. According to the review, presepsin is specific biomarker for bacterial infections compare with CRP and PCT. It may be useful to evaluate the empirical antibiotic outcome in sepsis condition.